Effect of a topical anaesthetic formulation on the cortisol response to surgical castration of unweaned beef calves. (28th July 2015) - McCarthy, D.; Lomax, S.; Windsor, P. A.; White, P. J.
Abstract : Impracticality and cost of existing pain management strategies during surgical castration of beef cattle have limited their widespread implementation on-farm. A farmer-applied topical anaesthetic formulation, originally developed and used commercially to mitigate the pain of mulesing in lambs, was investigated for its potential use for managing pain in surgically castrated calves. This formulation contained lidocaine, bupivacaine, adrenalin and cetrimide. In this study, 24 Angus bull calves were randomly allocated to (1) surgical castration (C, n= 8), (2) surgical castration with the post-operative application of topical anaesthetic (CTA, n= 8) and (3) sham castration/control (CON, n= 8). The experiment was conducted over 2 days, with treatment groups evenly represented across each day. Calves were habituated to handling before the experiment and blood samples were collected for plasma cortisol measurement at defined time periods before, at and post treatment, (at −0.5, 0 h, then +0.5, 1, 1.5, 2, 4 and 6 h). There was a significant effect of time on cortisol concentrations across all treatment groups ( P <0.01), with lowest concentrations at −0.5 and 6 h and peak concentration at 0.5 h being significantly higher than the cortisol response at 0 h. The effect of treatment was not significant ( P =0.077), however, there was a trend for CON calves to display lower cortisol concentrations than C and CTA calves and CTA calves to display lower cortisol concentrations than C calves. The mean area under the curve (AUC) of CON calves was significantly lower than those of C and CTA calves ( P =0.04), however, there was no significant difference between the AUCs of CTA and C calves. Immediate application of topical anaesthetic after surgical castration did not significantly reduce plasma cortisol concentrations. However, the trend for CTA calves to display lower cortisol concentrations than C calves warrants further investigation into the use of TA for pain relief of surgically castrated beef calves.